Improving the Community's Economy Influenced by Green Marketing through Post-Pandemic Travel Decisions - Nanik Wahyuningtiyas; Abdullah Syakur Novianto (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aims to examine how green marketing influences travel decisions, how green marketing influences the improvement of the community's economy, how the impact of the decision to travel on the progress of the community's economy, and how the effect of green marketing on the improvement of the community's economy through the decision To Travel in Malang Raya. Design/methodology/approach: The approach in this research is quantitative by using the SmartPLS analysis tool. Respondents are tourists who have visited tourist areas, as many as 175 respondents. Findings: The results of this study show that all independent variables have a positive and significant impact on dependent variables, and travel decision variables are proven to mediate the relationship between green marketing and improving the community's economy. Research limitations/implications: Because it is carried out through the google form the results obtained are not optimal. For further research, it is hoped that it will be more specific in explaining the variables of green marketing and can also add other variables that have become a phenomenon in the economic revival of the community in tourist areas after the covid-19 pandemic. Practical implications: Intensify efforts in the field of environmentally friendly tourism for economic improvement. Originality/value: This Paper is Original. Paper type: Research Paper